A province-wide childhood malignancy profiles in Indonesia (2010-2019): Yogyakarta Pediatric Cancer Registry - Supriyadi, Eddy; Purwanto, Ignatius; Armytasari, Inggar; Ritter, Julie; Widjajanto, Pudjo Hagung; Veerman, Anjo JP (Paediatrica Indonesiana, 2023)
Background The global burden of childhood cancer is poorly quantified, but it is estimated that 80% of all children with cancer live in low- and middle-income countries with cure rates of childhood cancer far lower than in high-income nations. Objective To describe the Yogyakarta Region pediatric cancer profile from 2010-2019 and compare it to that of a 2000-2009 study in the same setting. Methods This retrospective study of childhood cancer was conducted in patients aged £18 years and diagnosed in Dr. Sardjito General Hospital from 2010 to 2019. Pediatric cancer patient data were collected from hospital hardcopy and electronic medical records. An estimated annual average incidence rate of childhood cancer was calculated and the number of patients by their regions of origin were visualized. The number of childhood malignancies recorded is also compared by the number found in 2000-2009 study. Results There were 1,839 new cases registered in Yogyakarta Pediatric Cancer Registry during the study period. The mean age at diagnosis was 6.3 years and male-to-female ratio was 1.4: 1.0. Fifty-six% of cancers were diagnosed in the 0-5-years age group. The most common diagnosis category was leukemia, which accounted for 60% of all childhood malignancies. The three most common diagnoses were acute lymphoblastic leukemia (44%), acute myeloid leukemia (12%), and retinoblastoma (7%). The annual average incidence rates of leukemia and solid tumors were 26.8 and 17.5 per million, respectively. The number of patients registered in 2000-2009 study was 1,124 case. Therefore, there was an increase of 63.6% in the number of childhood malignancies registered in 2010-2019 compared to the 2000-2009 study. Conclusion There is an increase in the number of childhood malignancies registered in 2010-2019 compared to the 2000-2009 study. The number of patients referred to our hospital increased, indicating a more inclusive registry, better referral system, and better access to health care facility.